The Use of Information Technology in Primary Schools - Fozilov Ibrokhimjon Rakhimovich; Fozilov Jakhongir Ibrokhimovich (Zien Journals, 2021)
This article touches upon the prerequisites for the need to use tools and technologies in primary general education that contribute to the independent search for information, the development of skills and abilities to learn. This issue is acute in the conditions of modern reality, which was formed in the last third of the twentieth century, under the influence of information technology. The issues of the advantages of using IT in the classroom as a tool for creating conditions for the implementation of the problem-activity approach and the organization of project activities are considered.
Keywords: Information; technology; primary; classes